2021
DOI: 10.1016/j.ihj.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The study of novel inflammatory markers in takayasu arteritis and its correlation with disease activity

Abstract: Objectives Currently, erythrocyte sedimentation rate (ESR) and highly sensitive serum C-reactive protein (hsCRP) levels are used to monitor disease activity and guide therapy in Takayasu Arteritis (TA). However, non-specificity of these markers suggests the need for novel biomarkers. In this pilot study, we explore the role of novel biomarkers for evaluating disease activity in TA. Methods A total of 40 patients with TA were divided into active and stable disease groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Higher levels of IL-6 and IL-18 have been found in active TA patients, displaying a higher risk for restenosis. Moreover, determining interleukin levels might be useful when initiating biological therapy such as tocilizumab, an anti-IL-6 agent [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of IL-6 and IL-18 have been found in active TA patients, displaying a higher risk for restenosis. Moreover, determining interleukin levels might be useful when initiating biological therapy such as tocilizumab, an anti-IL-6 agent [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Th17, Treg-related cytokines such as IL-6, IL-10, IL-17, IL-18, and TNFα were abnormally expressed during TAK activity and were expected to become important markers for clinical assessment of disease activity. 23 Currently, studies focusing on the relationship between IL-10 and TAK are increasing. Nevertheless, the results from a single study were limited and may be affected by multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that T helper cell 17 (Th17 cell) was up‐regulated while Treg cells were down‐regulated, that is, a Th17/Treg imbalance, which was involved in the occurrence and development of TAK 22 . Th17, Treg‐related cytokines such as IL‐6, IL‐10, IL‐17, IL‐18, and TNF‐α were abnormally expressed during TAK activity and were expected to become important markers for clinical assessment of disease activity 23 . Currently, studies focusing on the relationship between IL‐10 and TAK are increasing.…”
Section: Discussionmentioning
confidence: 99%